2015
DOI: 10.1007/s13244-015-0446-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of thyroid nodules: a pictorial review

Abstract: Thyroid nodules are a common occurrence in the general population, and these incidental thyroid nodules are often referred for ultrasound (US) evaluation. US provides a safe and fast method of examination. It is sensitive for the detection of thyroid nodules, and suspicious features can be used to guide further investigation/management decisions. However, given the financial burden on the health service and unnecessary anxiety for patients, it is unrealistic to biopsy every thyroid nodule to confirm diagnosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 38 publications
0
62
0
5
Order By: Relevance
“…Meta‐analysis has shown that spongiform appearance on ultrasound has the highest diagnostic OR for benign characterization, and in addition to cystic nodules are the only 2 features that can prevent the need for an FNA biopsy . Similarly, reports estimate 10.0% and 99.7% sensitivity and specificity, respectively, for benign disease …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta‐analysis has shown that spongiform appearance on ultrasound has the highest diagnostic OR for benign characterization, and in addition to cystic nodules are the only 2 features that can prevent the need for an FNA biopsy . Similarly, reports estimate 10.0% and 99.7% sensitivity and specificity, respectively, for benign disease …”
Section: Resultsmentioning
confidence: 99%
“…In order to properly stratify risk of malignancy, ultrasound imaging findings should be corroborated by relevant findings on clinical history and examination. Commonly cited clinical features increasing likelihood of cancer include familial history of differentiated thyroid cancer, multiple endocrine neoplasia type II, or medullary thyroid carcinoma, any previous radiation exposure, male sex, age under 20 or over 60 years, a firm or fixed nodule, and rapid nodular growth . Physical examination findings that suggest malignancy include vocal cord paralysis, regional lymphadenopathy, dysphonia, and fixation to surrounding tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Intralesional punctate echogenic foci of calcification and intranodular vascularity may be detected . In case of a suspicious thyroid nodule, ultrasound‐guided biopsy is an important diagnostic tool …”
Section: Acquired Solid Massesmentioning
confidence: 99%
“…47 Suspicious imaging finding on US include a pronounced hypoechoic thyroid mass, a predominantly solid nature, disrupted eggshell calcifications, an irregular border, and "taller than wide" in shape. 48 Intralesional punctate echogenic foci of calcification and intranodular vascularity may be detected. 45,47 In case of a suspicious thyroid nodule, ultrasound-guided biopsy is an important diagnostic tool.…”
Section: Acquired Solid Masses Fibromatosis Collimentioning
confidence: 99%
See 1 more Smart Citation